2005
DOI: 10.1021/jp050821w
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Insights into the Sputtering of Thin Organic Films on Ag{111} Induced by C60 and Ga Bombardment

Abstract: Molecular dynamics computer simulations have been employed to model the bombardment of Ag{111} covered with three layers of C6H6 by 15 keV Ga and C60 projectiles. The study is aimed toward examining the mechanism by which molecules are desorbed from surfaces by energetic cluster ion beams and toward elucidating the differences between cluster bombardment and atom bombardment. The results show that the impact of the cluster on the benzene-covered surface leads to molecular desorption during the formation of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 51 publications
4
95
0
Order By: Relevance
“…This might be because the Cs + projectile is not sufficiently large and energetic to eject the silver ions. This result is consistent with that from the molecular dynamics simulation of the Ga + bombardment reported previously [11,12]. In addition, each carbon atom on C 60 + impact cannot be embedded into the silver substrate and interacts strongly with the polymer overlayer because the carbon atoms are easily deflected by silver atoms.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This might be because the Cs + projectile is not sufficiently large and energetic to eject the silver ions. This result is consistent with that from the molecular dynamics simulation of the Ga + bombardment reported previously [11,12]. In addition, each carbon atom on C 60 + impact cannot be embedded into the silver substrate and interacts strongly with the polymer overlayer because the carbon atoms are easily deflected by silver atoms.…”
Section: Resultssupporting
confidence: 91%
“…The mechanism of ion formation under cluster ion bombardment has yet to be completely explained. Theoretical and experimental studies, however, have shown the increased yield results from an overlap of low energy impact cascades of individual atomic components of cluster ions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the AA and DMPA maximum and minimum signal intensities remain nearly constant. The conservation of these molecular ion signals indicates that the ion bombardment does not create significant damage to the underneath layers, a result which is predicted by many molecular dynamics computer simulations of the bombardment process [10,28,29]. In sum- Figure 2. (a) Optical image of LB20 film with a crater in the middle which is created after C 60 ϩ depth profiling (the crater is the grey area, which is surrounded by blue uneroded area); (b) AFM measurements of LB20 films with a crater which is formed by C 60 ϩ depth profiling.…”
Section: Characterization Of Lb Films By Simsmentioning
confidence: 78%
“…Classical molecular dynamics (CMD) simulation has been performed to model ion sputtering of solids including metals [3] and organic thin films on inorganic substrates [4,5]. In these CMD simulations the damage to solid surface was made more reduction by cluster ion bombardments than by mono-atomic ion bombardments.…”
Section: Introductionmentioning
confidence: 99%